Levels of serum free thyroid hormones and cortisol in estrus, anoestrus and repeat breeding buffaloes - AGARWAL, R G; SHARMA, I J (The Indian Journal of Animal Reproduction, 2023)
No significant change in the values of serum protein and free thyroid (IT3 and IT4) honnones was observed in estrus, anoestrus and repeat breeding buffaloes. The serum cortisol levels though, at a low ebbs, but conspicuously higher in the oestrus than in the anoestrus and repeat breeding buffaloes.